Efektivitas Konsumsi Air Kelapa Muda Terhadap Penurunan Tekanan Darah Tinggi Padaibu Hamil Di Wilayah Kerja Puskesmas Saketi - Safitri, Lita; Galaupa, Resi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: Hypertension in pregnancy (HDK) is hypertension (blood pressure > 140/90 mmHg) that occurs in pregnancy > 20 weeks without a previous history of hypertension and without proteinuria. Preeclampsia is HDK accompanied by proteinuria. 300 ml of young coconut water therapy in the morning and evening for 2 weeks has an effect on reducing systolic and diastolic blood pressure in hypertension sufferers. Ambar Sari's research states that consuming 250 ml of young coconut water in the morning and evening for 2 weeks can reduce systolic blood pressure in the elderly. The aim of this research is to determine the benefits of consuming young coconut water in reducing high blood pressure in pregnant women in the Saketi Community Health Center working area. Methods: The method used is Quasi-experimental with a pre-post test research design in one group (one group pretest-psttest desigen). Data analysis used the Wicoxon Signed Rank Test. The population in this study were 20 pregnant women with hypertension Results: Based on the Wicoxon Signed Rank Test regarding the effect of giving young coconut water on reducing blood pressure in pregnant women in the Saketi Community Health Center Working Area, the Sig value was 0.000<0.05. Conclusion: There is an effect of giving young coconut water to pregnant women in the Saketi Health Center Working Area